ANALYSIS OF SUPPLIER SELECTION OF CORN STARCH RAW MATERIAL FOR CREAMER PRODUCTION ON KOPIKO AND TORABIKA ITEMS USING THE ANALYTICAL HIERARCHY PROCESS (AHP) METHOD (Case Study Of PT. Mayora Indah Tbk) - Maksi Prima Dewi; Hasmand Zusi (Dinasti Publisher, 2019)
This thesis is compiled to analyze supplier selection in Mayora Group, which is a Fast Moving Consumer Goods (FMCG) company, with the object of research using Corn Starch as raw material for making glucose creamer on Kopiko and Torabika items. Based on the criteria that have previously been used by the company, the researcher develops the criteria, sub-criteria for supplier selection and supplier classification as well as consistency test from respondents’ answers based on the level of experience and competence of the 4 departments related to the procurement process of raw material imports so that priority suppliers are selected from the current existing suppliers. The determination of supplier selection criteria is calculated based on the weight of the criteria. This criterion weighting is applied through the Analytical Hierarchy Process method. Based on the results of the study, 7 criteria are obtained for the supplier selection, in order of the highest to the lowest priority: Quality, Price, Document Completeness, Delivery, Service, Company Condition, and Geographical location. The value of consistency ratio (CR) in the pairwise comparison matrix of the criteria, sub-criteria, and alternatives of the results of the respondent’s questionnaire answers is within the tolerance limit, so that it is included in the valid and consistent category.